EphrinB-mediated reverse signalling controls junctional integrity and pro-inflammatory differentiation of endothelial cells - Liu, Hui; Hecker, Markus; Korff, Thomas (Thrombosis and haemostasis, 2017)
The EphB/ephrinB receptor-ligand system is pivotal for the development of the embryonic vasculature and for angiogenesis in the adult organism. We observed that (i) the expression of ephrinB2 and ephrinB1 is up-regulated in capillaries during inflammation, that (ii) these ligands are localised on the luminal endothelial surface, and that (iii) they interact with the ephrinB-receptor EphB2 on monocyte/macrophages. This study delineates the impact of ephrinB-mediated reverse signalling on the integrity and proinflammatory differentiation of the endothelium. To this end, in vitro analyses with human cultured endothelial cells reveal that knockdown of ephrinB2 or ephrinB1 impairs monocyte transmigration through the endothelium. While ephrinB2 but not ephrinB1 interacts with PECAM-1 (CD31) in this context, reverse signalling by ephrinB1 but not ephrinB2 elicits a c-Jun N-terminal kinase (JNK)-dependent up-regulation of E-selectin expression. Furthermore, treatment of endothelial cells with soluble EphB2 receptor bodies or EphB2-overexpressing mouse myeloma cells links ephrinB2 to PECAM-1 and induces its Src-dependent phosphorylation while diminishing Src homology phosphotyrosyl phosphatase-2 (SHP-2) activity and increasing endothelial cell permeability. We conclude that extravasation of EphB2 positive leukocyte populations is facilitated by lowering the integrity of endothelial cell junctions and enhancing the pro-inflammatory phenotype of the endothelium through activation of ephrinB ligands.